2019
DOI: 10.1055/s-0039-1683888
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotics during Intrauterine Balloon Tamponade Is Associated with a Reduction in Endometritis

Abstract: Objective To evaluate whether prophylactic antibiotics at the time of placement of an intrauterine balloon tamponade (IBT) is associated with a reduction in postpartum endometritis. Study Design Retrospective cohort study of patients who received an IBT from January 1, 2012, to December 12, 2016. Patients were included if the IBT remained in place at least 2 hours and excluded if chorioamnionitis was present. Patients who received prophylactic antibiotics at the time of IBT placement were compared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 9 publications
(12 reference statements)
0
5
0
Order By: Relevance
“…Wong et al did a retrospective cohort study and demonstrated that prophylactic antibiotics were associated with a reduction of postpartum endometritis. The overall incidence of endometritis was 5% in the group with prophylactic antibiotics vs. 26% in the group without [41]. Franklin-Dumon et al conducted a retrospective study to compare the incidence of endometritis between patients with PPH, with and without the use of IUTB.…”
Section: Discussionmentioning
confidence: 99%
“…Wong et al did a retrospective cohort study and demonstrated that prophylactic antibiotics were associated with a reduction of postpartum endometritis. The overall incidence of endometritis was 5% in the group with prophylactic antibiotics vs. 26% in the group without [41]. Franklin-Dumon et al conducted a retrospective study to compare the incidence of endometritis between patients with PPH, with and without the use of IUTB.…”
Section: Discussionmentioning
confidence: 99%
“…An Australian randomized clinical trial using the Bakri balloon as PPH prophylaxis for placenta previa following cesarean delivery utilized 1 g cefazolin and had a postpartum endometritis rate of 0% 57 . Another retrospective cohort study found the most common regimen for antibiotic prophylaxis for uterine balloon tamponade to be cefazolin 1 g every 8 hours, with patients receiving a median of 3 doses 58 …”
Section: Exploration and Instrumentation Of The Postpartum Uterusmentioning
confidence: 99%
“…57 Another retrospective cohort study found the most common regimen for antibiotic prophylaxis for uterine balloon tamponade to be cefazolin 1 g every 8 hours, with patients receiving a median of 3 doses. 58 Although various antibiotic regimens have been studied, there is little official guidance from national or worldwide organizations. The main recommendation comes from the WHO.…”
Section: Intrauterine Tamponade Balloonmentioning
confidence: 99%
“…Antibiotic prophylaxis (cephalosporin) and maintenance dose oxytocin should be administered throughout the tamponade time. (6,22,23,(25)(26)(27) After the infusion, the evaluation of the tamponade test begins. If within 30 minutes of infusion the drainage shows less than 50 mL, the prediction of successful tamponade is considered positive.…”
Section: When and How To Use An Intrauterine Balloon Tamponade?mentioning
confidence: 99%